Single Extracellular Vesicle Protein Analysis Using Immuno‐Droplet Digital Polymerase Chain Reaction Amplification. Issue 12 (12th March 2020) - Ko, Jina; Wang, Yongcheng; Carlson, Jonathan C. T.; Marquard, Angela; Gungabeesoon, Jeremy; Charest, Alain; Weitz, David; Pittet, Mikael J.; Weissleder, Ralph
Abstract: There is a need for novel analytical techniques to study the composition of single extracellular vesicles (EV). Such techniques are required to improve the understanding of heterogeneous EV populations, to allow identification of unique subpopulations, and to enable earlier and more sensitive disease detection. Because of the small size of EV and their low protein content, ultrahigh sensitivity technologies are required. Here, an immuno‐droplet digital polymerase chain reaction (iddPCR) amplification method is described that allows multiplexed single EV protein profiling. Antibody–DNA conjugates are used to label EV, followed by stochastic microfluidic incorporation of single EV into droplets. In situ PCR with fluorescent reporter probes converts and amplifies the barcode signal for subsequent read‐out by droplet imaging. In these proof‐of‐principle studies, it is shown that multiplex protein analysis is possible in single EV, opening the door for future analyses. Abstract : An immuno droplet digital polymerase chain reaction (iddPCR) method is developed for multiplexed single extracellular vesicles (EV) protein profiling. Antibody–DNA conjugates are used to label EV and labeled single EV are encapsulated into droplets. Using PCR, DNA barcodes are amplified for imaging‐based readout. It has shown that multiplex protein analysis is possible in single EV, opening the door for future analyses.